Policy Design on Regional Sports of Lubuklinggau City - Suratman, Suratman; Sartika, Sartika (Iapa Proceedings Conference, 2024)
This study aims to analyze and describe the policy design implemented by the Lubuklinggau City Government related to sports development to overcome the existing sports problems in the area. This study is important because it contributes to academic literature in the field of public policy. This research uses a descriptive qualitative approach to assess sports policy design in Lubuklinggau City. Data collection methods were conducted through field observations, in-depth interviews, and document analysis. Birkland's (2019) policy design theory categorizes policy design into five elements, which became the theoretical framework of this study. The research findings show that the Lubuklinggau City sports policy design has been prepared by considering field conditions and the need for increased development in the field of sports. This policy shows sociological suitability and considers the existing legal framework, socio-economic dynamics, and local potential. Based on the results and discussion, for the designed sports policy to overcome the existing problems, the government needs to involve the private sector, especially in increasing investment in the construction and maintenance of sports facilities and using comparative data to ensure the effectiveness of policy implementation. This study makes an important contribution to the literature on public policy design, especially in the field of regional sports.